B.T.C.H. nephrolithometry score: a novel scoring system to predict stone-free rate and complexity for ultrasound-guided percutaneous nephrolithotomy - Huang, Haiwen; Song, Haifeng; Ding, Tianfu; Xu, YangYang; Fan, Yunfei; Su, Boxing; Liu, Yubao; Hu, Weiguo; Xiao, Bo; Li, Jianxing (Frontiers in Medicine, 2025)
BackgroundThe existing scoring systems for percutaneous nephrolithotomy fail to adequately consider the influence of renal anatomy, leading to limited predictive accuracy. This study introduces and validates a novel B.T.C.H. nephrolithometry score, designed to better predict stone-free rates and complexity for ultrasound-guided percutaneous nephrolithotomy.MethodsB.T.C.H. nephrolithometry score evaluates four variables including stone burden, type of renal pelvis, calyces involved, and hydronephrosis. 134 patients who underwent ultrasound-guided percutaneous nephrolithotomy at Beijing Tsinghua Changgung Hospital were retrospectively analyzed. The inter-observer agreement was assessed using the linearly weighted kappa coefficient. The accuracy in predicting the stone-free rate was evaluated using receiver operating characteristic curve analysis. Spearman’s correlation analysis and Kendall’s W test were employed to examine the correlation between the scores of each scoring system and operative time, the number of tracts and CDC scores.ResultsThe overall stone-free rate was 52.99%. The stone-free rates in low (4–8 points), medium (9–12 points), and high (13–15 points) B.T.C.H. scores were 91.9, 24.6, and 0%, respectively. The B.T.C.H. nephrolithometry score had an AUC of 0.909 for predicting stone-free rate, outperforming both the GSS (AUC = 0.761) and the S.T.O.N.E. nephrolithometry score (AUC = 0.763). The B.T.C.H. nephrolithometry score were positively correlated with operative time, the number of tracts and CDC scores.ConclusionB.T.C.H. nephrolithometry score is a suggested novel scoring system for ultrasound-guided percutaneous nephrolithotomy, which had superior prediction of stone-free rate and positive correlation with operative time, the number of tracts, and postoperative CDC scores.